Enrichment, sources, and distributions of toxic elements in the farming land's topsoil near a heavily industrialized area of central Bangladesh, and associated risks assessment. Issue 4 (April 2023) - Moni, Fahmida Najnin; Miazi, Md. Samir Ahmed; Kabir, Md. Humayun; Shammi, Rifat Shahid; Islam, Md. Sirajul; Islam, Md. Shafiqul; Sarker, Md. Eusuf; Khan, Md. Mehedi Hasan; Ahammed, Md. Shakir; Siddique, Md. Abu Bakar; Kormoker, Tapos
Abstract: Toxic element accumulation in the surrounding soils of the advanced industry- and agriculture-oriented areas may lead to severe environmental degradation and harmful impact on inhabitants. This work examined the concentration of some concerned toxic elements (Cr, Pb, Cd, Cu, As, and Ni) in the representative topsoil from 10 industrially contaminated sites in central Bangladesh (Narayanganj district) using an Inductively Coupled Plasma Mass Spectrometer concerning the probable ecological and human health risks. The mean concentrations (mg/kg) of the elements were found in the order of Ni (58.1 ± 11.8) > Pb (34.1 ± 14.3) > Cr (32.1 ± 6.77) > Cu (14.5 ± 3.30) > Cd (2.74 ± 1.08) > As (1.49 ± 0.43). The findings pointed out that diversified manmade events enhanced the intensities of elemental contamination through the studied sites. Source analysis showed that Cr, Pb, As, and Cd may originate from industrial wastewater and agricultural activities, whereas Cu and Ni came from natural sources. The geo-accumulation index level for Cd (1.70–3.39) was determined as grade 3 (moderately to strongly polluted), the enrichment factor score for Cd (13.9) fell in the very severe enhanced category (cluster 5), and the highest contamination factor value was found for Cd (15.7). The contamination degree values for all the tested elements signify a moderate to severe contamination grade; conversely, pollution load index levels depicted the nonexistence of elemental pollution. The assessment revealed serious Cd pollution in agricultural soils and moderate to significant potential ecological risk for the rest of the examined toxic elements. Furthermore, hazard index values exceeded the safe exposure levels, indicating that there was potential non-carcinogenic risk in the soils for children and adults. Ingestion exposure had much higher carcinogenic risk values than inhalation and cutaneous exposure, and children are exposed to considerable carcinogenic hazards. Therefore, it is suggested that the harmful practices that expose this farming soil to contaminants should be stopped immediately and effective environment-friendly techniques of waste management and effluent treatment should be employed in the study area. Graphical abstract: Image 1 Highlights: Enrichment of toxic elements (TEs) in industry-impacted farming soils was assessed. TEs concentrations exceed the standard limit and follow the order Ni > Pb > Cr > Cu > Cd > As. Origin of TEs is both anthropogenic (Cr, Pb, As, and Cd) and natural (Cu and Ni). Severe Cd pollution and moderate ecological risk of TE in farming soils were observed. TEs impose both non-carcinogenic (children & adults) and carcinogenic (children) risks.